Validation of Superiority of p40 over p63 in Differentiating Squamous Cell Carcinoma and Adenocarcinoma Lung - Thamtam, Vamshi; Uppin, Shantveer; Hui, Monalisa; Kumar, N; Bhaskar, K; Bala, Stalin; Sadashivudu, G; Paramjyothi, G (Indian Journal of Medical and Paediatric Oncology, 2020)
In this era of targeted therapy, it is important to distinguish the various subtypes of nonsmall cell lung carcinoma (NSCC). Diagnosis based on morphology alone is challenging in poorly differentiated carcinomas and core biopsies. Immunohistochemistry (IHC) helps in specifying the lineage for the subtype of NSCC. Till date, p63 is the most frequently used and sensitive marker for squamous cell carcinoma (SQCC). However, it is not specific and stains a subset of adenocarcinoma (ADC). Thus, a more reliable and specific marker is required for the diagnosis of SQCC.The objective of the study was to validate the diagnostic utility of p40 over p63 in differentiating pulmonary SQCC from ADC and NSCC-not otherwise specified (NOS).A total of 123 cases of NSCC were initially reviewed and subtyped blinded to the results of IHC. This was followed by a review of IHC slides which included p63, p40, thyroid transcription factor 1, Napsin-A, cytokeratin (CK) 5/6, and CK7.There were 64 ADC, 19 SQCC, and 40 NSCC-NOS. IHC helped to confirm the morphological diagnosis in 62/64 ADCs and19/19 SQCCs. IHC classified the cases of NSCC-NOS into NSCC favoring ADC – 12 cases, NSCC favoring SQCC – 10 cases, and NSCC favoring AD-SQCC – 4 cases. Both p63 and p40 showed near equal sensitivity for SQCC (100% and 97%, respectively), whereas p63 showed far lower specificity when compared to p40 (51.3% vs. 100%).The present study confirms and validates that p40 is equally sensitive but highly specific than p63 in detecting SQCC. Hence, we recommend the routine use of p40 instead of p63 for the definite categorization of NSCC of the lung.
Keywords: Immunohistochemistry; lung; nonsmall cell carcinoma; p40; p63